Investigação dos impactos nas concepções não-newtonianas de licenciandos e egressos de Física em relação aos conceitos de Força e Movimento - Uibson, José; Frei, Fernando [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (UNESP), Faculdade de Ciências, campus de Bauru., 2023)
Practices that are considered traditional and poorly contribute to students’ learning persist in the teaching of Physics. Thus, this article aimed at understanding the non-Newtonian conceptions of undergraduates and graduates in a Physics Degree course in relation to the concepts of Force and Motion, in addition to analyzing possible influences on these conceptions when students were exposed to a Computational Simulation and a textbook, applied under the same conditions (freely and for a short period of time). This is a quantitative study with a quasi-experimental design, with a control group and an experimental one. In both groups, a reduced version of the Force Concept Inventory (FCI) was applied in the construction of the data, both in the pre-test and in the post-test. In addition to the analysis of conceptions, the normalized learning gain and the effect size were used. The results indicate that, on average, the proposed treatments did not significantly influence the students' conceptions.

Persistem no ensino de Física práticas consideradas tradicionais e que pouco contribuem para a aprendizagem dos alunos. Assim, este artigo teve por objetivo conhecer as concepções não-newtonianas de licenciandos e egressos de um curso de Licenciatura em Física com relação aos conceitos de Força e Movimento, além de analisar possíveis impactos nessas concepções quando os alunos foram expostos a uma Simulação Computacional e a uma apostila, aplicados nas mesmas condições (de forma livre e por curto intervalo de tempo). Trata-se de uma pesquisa quantitativa de delineamento quase-experimental com grupo controle e experimental. Em ambos os grupos foi aplicada uma versão reduzida Force Concept Inventory (FCI) na construção dos dados, tanto no pré-teste quanto no pós-teste. Além das análises das concepções, foi utilizado o ganho normalizado de aprendizagem e o tamanho do efeito. Os resultados indicam que, em média, os tratamentos propostos não influenciaram significativamente as concepções dos alunos.
Investigating the impacts on non-Newtonian conceptions of Physics undergraduates and graduates in relation to the concepts of Force and Motion
Keywords: Physics teaching; Non-Newtonian conceptions; Force and motion; FCI.; Ensino de física; Concepções não-newtonianas; Força e movimento; FCI.